2019
DOI: 10.1038/s41467-019-12935-7
|View full text |Cite
|
Sign up to set email alerts
|

Procr-expressing progenitor cells are responsible for murine ovulatory rupture repair of ovarian surface epithelium

Abstract: Ovarian surface epithelium (OSE) undergoes recurring ovulatory rupture and repair. The OSE replenishing mechanism post ovulation remains unclear. Here we report that the expression of Protein C Receptor (Procr) marks a progenitor population in adult mice that is responsible for OSE repair post ovulation. Procr+  cells are the major cell source for OSE repair. The mechanism facilitating the rapid re-epithelialization is through the immediate expansion of Procr+  cells upon OSE rupture. Targeted ablation of Proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…Protein C receptor (Procr) marks adult stem/progenitor cells in various tissues, including the mammary gland (Wang et al, 2015a), vascular endothelial cells (Yu et al, 2016), pancreatic islet (Wang et al, 2020), ovarian surface epithelium (OSE) (Wang et al, 2019), and hematopoietic system (Balazs et al, 2006). Procr encodes a single-pass transmembrane protein (Fukudome and Esmon, 1994).…”
Section: Ll Open Accessmentioning
confidence: 99%
See 3 more Smart Citations
“…Protein C receptor (Procr) marks adult stem/progenitor cells in various tissues, including the mammary gland (Wang et al, 2015a), vascular endothelial cells (Yu et al, 2016), pancreatic islet (Wang et al, 2020), ovarian surface epithelium (OSE) (Wang et al, 2019), and hematopoietic system (Balazs et al, 2006). Procr encodes a single-pass transmembrane protein (Fukudome and Esmon, 1994).…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Upon binding to its ligand Protein C, Procr activates several intracellular signaling, resulting in increased proliferation and survival in various tissues (Cheng et al, 2003;Gramling et al, 2010;Wang et al, 2018). Indeed, Procr+ OSE cells proliferate faster than Procr-OSE cells (Wang et al, 2019) and Procr+ endothelial cells exhibited more robust proliferation than Procrendothelial cells (Yu et al, 2016).…”
Section: Ll Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…Procr, also known as endothelial protein C receptor (EPCR), is a single-pass transmembrane protein with reported function in anticoagulation, inflammation and hematopoiesis [1][2][3][4][5]. Our previous studies have identified Procr as an adult stem cell marker of multiple tissues, such as the mammary gland epithelium, blood vasculature, ovary epithelium and pancreatic islets [6][7][8][9]. Moreover, almost half of aggressive triple negative breast cancer (TNBC) cases have been shown to harbor robust PROCR expression [10], indicating that PROCR could be a useful biomarker as well as a potential treatment target.…”
Section: Introductionmentioning
confidence: 99%